The Role of Communicators in Instilling Moral Values in Adolescents at RPTRA Malinjo, South Jakarta - Dwi Kartikawati (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2022)
The cultivation of character values ​​is very urgently needed in forming virtuous teenagers. Character education will strengthen the moral construction of teenagers so that they are not easily swayed in the face of various trials in their lives. The success of the planting cannot be separated from the role of communicators who have special characteristics as communicators. This research focuses on RPTRA Malinjo Jakarta, which is led by Pembina as a communicator. The target in inculcating character values ​​is aimed at teenagers considering that adolescence is a period of searching for identity and is a period that is vulnerable to various kinds of good or bad influences in their environment. Literature review used in this research is the concept of role, the concept of communicator characteristics, the concept of inculcating character values, the concept of youth. The research approach departs from a qualitative approach with data collection techniques with in-depth interviews with RPTRA coaches who meet the characteristics of communicators who carry out their roles in these duties and also to young people in RPTRA. So that the results of the study indicate that the role of the communicator, namely the RPTRA coach in instilling character values, carries out two roles overall. who are credible, have attractiveness and have the power to instill ethical values ​​in various ways and methods. The research approach departs from a qualitative approach with data collection techniques with in-depth interviews with RPTRA coaches who meet the characteristics of communicators who carry out their roles in these duties and also to young people in RPTRA. So that the results of the study indicate that the role of the communicator, namely the RPTRA coach in instilling character values, carries out two roles overall. who are credible, have attractiveness and have the power to instill ethical values ​​in various ways and methods. The research approach departs from a qualitative approach with data collection techniques with in-depth interviews with RPTRA coaches who meet the characteristics of communicators who carry out their roles in these duties and also to young people in RPTRA. So that the results of the study indicate that the role of the communicator, namely the RPTRA coach in instilling character values, carries out two roles overall. who are credible, have attractiveness and have the power to instill ethical values ​​in various ways and methods.